The Urban Landscape of the ‘Fourth City’ (diségno, 2024)
The proposed contribution is offered as an operational reflection (drawings and text), on the becoming of the contemporary Hyperville in the era of the Anthropocene. Theorising, on the one hand, the status of the Fourth City as a design variant of the contemporary city and, on the other, a protocol of representation that interrogates the meaning of designing today. The description of the city becomes the premise for a different approach to the architectural question, in which the ethical and aesthetic category of the ‘urban landscape’ shifts the designer’s attention from the architectural object to the representation of the landscape.
Keywords: Urban project; Ground; Fourth City; Hot digital; Urban Landscape